Perspectives of interns on integration of ayurveda and allopathy in health care: a qualitative study - Dushyanth, P.; Majjige, Sumanth Mallikarjuna (International Journal Of Community Medicine And Public Health, 2017)
Background: The objective of the study was to generate perspectives of Interns on integration of Ayurveda and Allopathy in health care through focus group discussion. Methods: Two focused group discussion (FGD) sessions with Interns (N=15) of our institution was conducted during October 2014. Interns were selected based on convenience sampling method. Both FGD was conducted by the same moderator after taking consent from the participants. Sessions were audio recorded and later it was transcribed and analyzed. Results: The discussion showed that they had limited knowledge about Ayurveda which was from reading books and interacting with Ayurveda interns during the postings. There was mixed opinion regarding the integration of two systems of medicine. They opined that both the systems should not be integrated because Ayurveda is not based on evidence based research like Allopathy. Majority of interns opined that integration will benefit the patients as many chronic diseases can be effectively treated with Ayurveda. They suggested that providing knowledge about Ayurveda to Allopathy doctors at syllabus and training level will help in giving proper advice to patients on opting for ayurvedic treatment. Everyone had a positive opinion regarding inclusion of ayurvedic doctors in managing health programs as it increases the man power for effective management. Conclusions: Integration of both systems will benefit the patient. Quality research evidence on specific diseases which are effectively treated in Ayurveda will encourage Allopathy doctors to recommend ayurvedic treatment. Thus, considering alternative medicine as an additional medicine will have a positive impact on effective health care.